In Vivo Validation of a Computationally Predicted Conserved Ath5 Target Gene Set - Del Bene, Filippo; Ettwiller, Laurence; Skowronska-Krawczyk, Dorota; Baier, Herwig; Matter, Jean-Marc; Birney, Ewan; Wittbrodt, Joachim (PLOS Genetics, 2007)
So far, the computational identification of transcription factor binding sites is hampered by the complexity of vertebrate genomes. Here we present an in silico procedure to predict target sites of a transcription factor in complex genomes using its binding site. In a first step sequence, comparison of closely related genomes identifies the binding sites in conserved cis-regulatory regions (phylogenetic footprinting). Subsequently, more remote genomes are introduced into the comparison to identify highly conserved and therefore putatively functional binding sites (phylogenetic filtering). When applied to the binding site of atonal homolog 5 (Ath5 or ATOH7), this procedure efficiently filters evolutionarily conserved binding sites out of more than 300,000 instances in a vertebrate genome. We validate a selection of the linked target genes by showing coexpression with and transcriptional regulation by Ath5. Finally, chromatin immunoprecipitation demonstrates the occupancy of the target gene promoters by Ath5. Thus, our procedure, applied to whole genomes, is a fast and predictive tool to in silico filter the target genes of a given transcription factor with defined binding site.